Limited Resection Is Associated With a Higher Risk of Locoregional Recurrence than Lobectomy in Stage I Lung Adenocarcinoma With Tumor Spread Through Air Spaces. (August 2019) - Kadota, Kyuichi; Kushida, Yoshio; Kagawa, Seiko; Ishikawa, Ryou; Ibuki, Emi; Inoue, Kosuke; Go, Tetsuhiko; Yokomise, Hiroyasu; Ishii, Tomoya; Kadowaki, Norimitsu; Haba, Reiji
Abstract : A growing number of independent studies have validated spread through air spaces (STAS) to be a predictor of worse prognosis in lung adenocarcinoma. To investigate the prognostic significance of STAS according to types of surgery and locations of recurrence, and the association between STAS and anti-anaplastic lymphoma kinase (ALK) expression, we analyzed a series of 735 Japanese patients with resected lung adenocarcinoma, which was restaged according to the 8th edition of TNM staging system. STAS was defined as tumor cells within air spaces in the lung parenchyma beyond the edge of the main tumor. Tumors were classified according to the 2015 WHO lung tumor classification. Recurrence-free probability and overall survival were analyzed using the log-rank test and the Cox proportional hazards model. STAS was observed in 247 patients. STAS was more frequently identified in ALK-positive tumors ( P =0.020). STAS was an independent prognostic factor of a worse recurrence-free probability in all patients (hazard ratio [HR]=5.33, P <0.001) and in stage I patients (HR=6.87, P <0.001). STAS was an independent prognostic factor of a worse overall survival in all patients (HR=2.32, P <0.001) and in stage I patients (HR=2.85, P <0.001). In stage I patients with STAS, compared with lobectomy, limited resection was associated with a significantly higher risk of any recurrence ( P =0.010) and locoregional recurrence ( P =0.002). We have demonstrated that, in lung adenocarcinoma with STAS, limited resection was associated with a significantly higher risk of recurrence (especially locoregional recurrence) than lobectomy was. Abstract : Supplemental Digital Content is available in the text.